Ghrelin and obestatin expression in oral squamous cell carcinoma: an immunohistochemical and biochemical study - Alnema, Manar M.; Aydin, Suleyman; Ozkan, Yusuf; Dagli, Adile F.; Ozercan, Hanifi I.; Yildirim, Nezahat; Donder, Emir (Springer, 2010)
The underlying molecular mechanism of carcinogenesis in oral squamous cell carcinoma (OSCC) is poorly understood and appears to be controlled on many genetic, environmental, and hormonal factors. Obestatin and ghrelin, two recently discovered hormones, are co-expressed in endocrine cells. The purpose of this investigation was to examine the immunohistochemical features of OSCCs in relation to the tissue concentration of ghrelin and obestatin. The association between OSCC and Epstein Barr Virus (EBV) status was also explored. The expression of ghrelin and obestatin was examined by immunohistochemistry and immunoassay in oral biopsy specimens: 10 benign squamous epithelial cell samples, 10 microinvasive squamous cell carcinomas, and seven well-differentiated and seven poorly differentiated OSCCs. The presence of EBV was evaluated in these samples using immunohistochemistry. The concentrations of ghrelin and obestatin in tissue homogenates were measured by RIA and ELISA, respectively. Squamous cell carcinomas and benign tissue samples were positive for anti-EBV antibody, and obestatin and ghrelin were shown to be co-expressed in all stratified squamous epithelium samples. Expression of ghrelin and obestatin was decreased or absent in OSCCs in relation to the invasiveness of the carcinoma; ghrelin and obestatin levels in cancerous tissue homogenates were lower than in benign tissue homogenates. These results indicate that the concentrations and distribution of immunoreactive obestatin and ghrelin might be helpful in distinguishing OSCC from benign tumors. Maintaining normal levels of these hormones might be required for regulation of normal cell division. However, detailed studies will be required for better understanding of the complex mechanism of carcinogenesis relating to OSCCs.
Keywords: Oral squamous cell carcinoma; Ghrelin; Obestatin; Epstein barr virus